Akibat Hukum Pemutusan Hubungan Kerja Secara Sepihak Bagi Guru Pada Yayasan Pendidikan Pasca Putusan MK No.91/PUU-XIX/2021 Tentang Pengujian Formil Undang-Undang No.11 Tahun 2020 Tentang Cipta Kerja Terhadap Undang-Undang Dasar 1945 (Studi Pada Yayasan Pendidikan Nasional Khalsa Medan) - Dewa Rohid; Maswandi Maswandi; Beby Suryani Fitri (Universitas Medan Area, 2023)
A specified time work agreement (PKWT) is a work agreement between workers/laborers and employers to enter into a work relationship within the time specified in Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation. The problem in this research is what are the legal consequences for unilateral termination of employment carried out by the Khalsa Medan National Education Foundation for workers who default on work agreements for a certain time that have been agreed upon, and how to resolve them. This study uses normative juridical legal research methods, the nature of the research is descriptive-analytical with a library research approach (Library Research) and field studies at the Khalsa National Education Foundation in Medan, then analyzed qualitatively. The results of the study show that unilateral termination of employment for teachers must be in accordance with statutory regulations with the aim of providing legal protection to each teacher in order to obtain the right to compensation for years of service obtained from the Khalsa Medan National Education Foundation.